New estimations about the order of growth and the type of meromorphic functions in the complex plane - Belaïdi, BENHARRAT; Latreuch, ZINELAÂBIDINE (An. Univ. Oradea, Fasc. Mat, 2013)
In this paper, we will give sufficient conditions to obtain new estimates about the order of growth and the type of meromorphic functions in the complex plane. We give also some examples to explain the sharpness of these estimations.
Keywords: Meromorphic function; Order of growth; Type